2018
DOI: 10.1001/jamadermatol.2018.0592
|View full text |Cite
|
Sign up to set email alerts
|

Interest and Uptake ofMC1RTesting for Melanoma Risk in a Diverse Primary Care Population

Abstract: Importance Germline variants in the MC1R gene are common and confer moderate melanoma risk in those with varied skin types. Approaches to precision skin cancer prevention that include genetic information may promote risk awareness and risk reduction in the general population, including Hispanics. Objective To examine prevalence of interest in and uptake of MC1R testing in the general population and examine patterns across demographic and skin cancer risk factors. Design A randomized controlled trial examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 56 publications
2
62
0
Order By: Relevance
“…In previous analyses, participants who completed testing reported high levels of interest and engagement in their test feedback results and reported determination to improve sun protection behavior after receiving feedback, and such determination was significantly higher in those who received higher risk feedback, compared to average risk feedback two weeks after test receipt [55]. Those with a sunburn history were more likely to complete testing [69]. It may also be that there are elements of behavioral impact that were not measured in the current study that might ultimately contribute to the personal and health utility of MC1R feedback, such as longer-term behavioral habits, improved engagement and perceived control over sun protection choices.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In previous analyses, participants who completed testing reported high levels of interest and engagement in their test feedback results and reported determination to improve sun protection behavior after receiving feedback, and such determination was significantly higher in those who received higher risk feedback, compared to average risk feedback two weeks after test receipt [55]. Those with a sunburn history were more likely to complete testing [69]. It may also be that there are elements of behavioral impact that were not measured in the current study that might ultimately contribute to the personal and health utility of MC1R feedback, such as longer-term behavioral habits, improved engagement and perceived control over sun protection choices.…”
Section: Discussionmentioning
confidence: 91%
“…As reported previously [69], 1998 primary care patients were approached, 917 (46%) agreed to be screened for eligibility, and of the 726 patients who were eligible for the study, 621 (86%) consented to study participation; 21 did not complete the baseline assessment. Study acceptance was higher in non-Hispanic whites compared to Hispanics, and those with higher (>high school) compared to lower educational attainment (<high school) but did not differ on other demographic factors [69]. Further, those with higher perceived skin cancer risk and those with greater interest in learning about genes were more likely to participate.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, interventions could be more targeted and with even more promising results. Finally, we recommend that future studies develop and evaluate the impact of sun-protective interventions, as previous research have shown their potential to promote sun protection in recreational settings (51)(52)(53). Manuscript to be reviewed Manuscript to be reviewed Manuscript to be reviewed 1 Manuscript to be reviewed Manuscript to be reviewed Manuscript to be reviewed Manuscript to be reviewed…”
Section: Resultsmentioning
confidence: 99%
“…Data were collected as part of a randomized controlled trial (NCT03130569) examining interest, uptake, and outcomes associated with an offer of testing for MC1R gene variants associated with increased melanoma risk (10). Study enrollment methods have been described previously (13,14). In brief, 600 participants were recruited from a primary care clinic in Albuquerque, New Mexico (Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%